2015
DOI: 10.1152/japplphysiol.00307.2015
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial phasic function interacts to support left ventricular filling during exercise in healthy athletes

Abstract: We studied the contribution of phasic left atrial (LA) function to left ventricular (LV) filling during exercise. We hypothesized that reduced LV filling time at moderate-intensity exercise limits LA passive emptying and increases LA active emptying. Twenty endurance-trained males (55 ± 6 yr) were studied at rest and during light- (∼100 beats/min) and moderate-intensity (∼130 beats/min) exercise. Two-dimensional and Doppler echocardiography were used to assess phasic volumes and diastolic function. LV end-dias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 31 publications
3
27
0
Order By: Relevance
“…Conduit LA function represent the ability to passively transfer blood into the LV. The LA active function shows the LA contraction during the last diastolic phase that enables up to 30% of LV stroke volume in athletes …”
Section: Introductionmentioning
confidence: 99%
“…Conduit LA function represent the ability to passively transfer blood into the LV. The LA active function shows the LA contraction during the last diastolic phase that enables up to 30% of LV stroke volume in athletes …”
Section: Introductionmentioning
confidence: 99%
“…For horses and humans in sinus rhythm (SR), the active contribution from the atria can account for approximately 10%‐20% of ventricular stroke volume at rest, but the absent atrial pumping function in AF patients rarely clinically affects hemodynamic parameters at rest. However, the atrial pumping function becomes more important as the intensity of exercise increases, because the relative portion of passive filling is decreased because of tachycardia . A marked decrease in cardiac output therefore can be expected in AF patients during exercise and tachycardia …”
Section: Introductionmentioning
confidence: 99%
“…However, the atrial pumping function becomes more important as the intensity of exercise increases, because the relative portion of passive filling is decreased because of tachycardia. 14 A marked decrease in cardiac output therefore can be expected in AF patients during exercise and tachycardia. 15 Previous studies have reported disproportional tachycardia in AF horses during exercise, 3,16,17 and 1 study also reported a broadening of QRS complexes and abnormal ventricular activation.…”
mentioning
confidence: 99%
“…This emphasizes the physiological need for an increased early LV filling as an adaptation to exercise. 30 In HFpEF, limited conduit function at rest is likely to exaggerate during exercise and might no longer be compensated for by active LA contraction, impacting on LV early filling, LV stroke volume, cardiac output, and ultimately exercise capacity. …”
mentioning
confidence: 99%